Psychosocial influence of hearing impairment on the interpersonal behavior of youths with hearing impairment in Oyo State, Nigeria (2013)
Individuals with hearing impairment are confronted with a lot of problems due to the condition of their disability. This has a negative impact on their social and psychological well-being with multiplying effect on their interpersonal relationship. Therefore, this study investigated the psycho-social influence of hearing impairment on interpersonal behavior of youths with hearing loss. Methodology The study adopted a survey research design. A sample consisting of 211 participants with hearing loss were purposively selected from the Federal College of Education (Special) Oyo, Nigeria. A questionnaire, part of Psycho-social Competence Scale (PCS), was used for data collection with reliability coefficient of 0.72. Results The findings revealed that hearing impairment affects social interaction of youths with hearing impairment, hearing loss affects emotional well-being of youths with hearing impairment and youths with hearing impairment feel inferior in company of persons without hearing impairment. Based on this, it was recommended that a friendly home environment should be made and youths with hearing impairment should be advised to accept their loss and take it as a challenge that can be used to achieve a better end and the society should have right attitude and beliefs toward youths with hearing impairment.